Dampak Kekerasan Verbal dan Fisik dalam Keluarga terhadap Perilaku Remaja: Studi Kasus Melalui Konseling Kelompok - Nurlaeli, Siti; Abdi, Sofyan; Hasna, Afra; Putri, Najla Hana; Syamsiah, Nur (Blantika: Multidisciplinary Journal, 2025)
This study aims to describe the impact of family violence on adolescents based on the results of group counseling on 15-year-old male adolescent subjects. Adolescents who experience verbal and physical violence in the family face major challenges in their emotional and behavioral development with a qualitative approach and case study, data collected through participant observation and in-depth interviews. The findings indicate that violence from parents contributes to identity crises, emotional disturbances, and difficulties in establishing social relationships. Group counseling allows subjects to realize inner wounds, build new hopes, and strengthen emotional regulation. Through a qualitative approach and case study method, this article examines the psychological dynamics that emerge in subjects and the role of counseling in facilitating self-reflection and behavioral change. Group counseling has been shown to provide space for self-expression and reflection, becoming one of the effective approaches in helping psychological recovery.